Al-cu-mn-c alloy with low aging heat treatment sensitivity and preparation method and application thereof
Patent Information
- Application Number
- CN202410209378.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-26
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2044-02-26
AI Technical Summary
[0022](1)提高析出相非均匀形核能力:采用机械合金化工艺实现石油焦在Al-Cu-Mn合金中均匀弥散分布,石油焦中微量Mg元素在Al/C相界的原子偏聚,这是单独添加C颗粒与Mg粉所不能实现的,有助于增加析出相的形核质点,形成超细沉淀相,提高材料强度,改善材料塑性。
Smart Images

Figure CN117947322B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aluminum alloy material preparation technology, specifically relating to an Al-Cu-Mn-C alloy with low aging heat treatment sensitivity, its preparation method and application. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] The 2xxx series (Al-Cu) alloys are among the earliest studied series in the history of aluminum alloys. The addition of copper as an alloying element to aluminum induces age hardening, laying the foundation for the application of 2xxx series aluminum alloys in the aerospace field. The 2xxx series mainly includes Al-Cu-Mn alloys, Al-Cu-Mg alloys, and Al-Cu-Li alloys, all of which achieve strengthening through heat treatment. Their main characteristics include high strength, low density, excellent machinability, and good heat resistance.
[0004] Currently, the addition of trace elements to form different types of precipitates is commonly used to optimize the overall mechanical properties of 2xxx series aluminum alloys. 2xxx series aluminum alloys mainly have two types of precipitates: one is non-equilibrium metastable phases, existing in the supersaturated solid solution obtained after solution treatment and quenching, including δ′, δ′, δ′, T2′, S′, etc.; the other is equilibrium phases, precipitates formed through solution treatment and aging, including δ, β, θ, T1, T2, T… B The precipitates include S, R, and T. The S (Al₂CuMg) phase is the most prevalent precipitate in 2xxx series aluminum alloys and also the most important strengthening phase during aging treatment. As aging progresses, the S phase gradually grows and agglomerates, forming a lath-like structure, leading to a decrease in material plasticity. Therefore, controlling the precipitation behavior of the strengthening phase in 2xxx series aluminum alloys and preventing the agglomeration and growth of the second phase is crucial for further improving the overall mechanical properties of 2xxx series alloys. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a low-aging-heat-treatment-sensitive Al-Cu-Mn-C alloy, its preparation method, and its applications. This invention incorporates petroleum coke during the mechanical alloying process of the Al-Cu-Mn alloy. This promotes the uniform and dispersed precipitation of the precipitated phase, inhibits the growth and agglomeration of the precipitated phase, enhances the dispersion strengthening effect of the precipitated phase, improves the material's plasticity, and achieves the preparation of a high-strength, high-toughness Al-Cu-Mn-C alloy. The petroleum coke used in this invention is a byproduct obtained from the coking process of heavy oil during petroleum refining. It is inexpensive and abundant. Through mechanical alloying, it achieves uniform dispersion distribution in the aluminum alloy matrix, coupling fine-grain strengthening, solid solution strengthening, and load-bearing strengthening effects, showing promising prospects for industrial application.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solution:
[0007] In a first aspect, the present invention provides an Al-Cu-Mn-C alloy with low aging heat treatment sensitivity, comprising the following components by weight percentage: 2% to 5% petroleum coke, with the balance being Al-Cu-Mn matrix material.
[0008] Preferably, the Al-Cu-Mn matrix material comprises the following components by weight percentage: Cu 1.0% to 3.8%, Mn 0.1% to 0.5%, with the balance being Al and incidental elements.
[0009] Preferably, the weight ratio of petroleum coke to Cu is greater than 0.8.
[0010] Petroleum coke contains trace amounts of magnesium (Mg). Adding petroleum coke to Al-Cu-Mn alloys not only introduces carbon (C) particles but also facilitates atomic segregation of Mg at the Al / C phase boundaries during mechanical alloying. This increases the number of nucleation sites for the precipitated phases, effectively enhancing the heterogeneous nucleation ability of the Al-Cu-Mn alloy. Simultaneously, the Al / C phase boundaries pin the atomic diffusion in the precipitated phases, inhibiting the growth and aggregation of the precipitated phases, improving the dispersion strengthening effect of the precipitated phases, and enhancing the material's plasticity, thus enabling the preparation of high-strength and high-toughness Al-Cu-Mn alloys.
[0011] In a second aspect, the present invention provides a method for preparing an Al-Cu-Mn-C alloy with low aging heat treatment sensitivity as described in the first aspect, comprising the following steps:
[0012] S1. Petroleum coke and Al-Cu-Mn matrix material powder are ball-milled and mixed to obtain Al-Cu-Mn-C alloy powder;
[0013] S2. Press the Al-Cu-Mn-C alloy powder and process it to obtain Al-Cu-Mn-C alloy products.
[0014] S3. The Al-Cu-Mn-C alloy product is solution-treated, then water-quenched, and then artificially aged. After artificial aging, it is naturally cooled to obtain the Al-Cu-Mn-C alloy with low aging heat treatment sensitivity.
[0015] Preferably, the Al-Cu-Mn matrix material powder is an atomized powder with an average particle size of 1–200 μm.
[0016] Preferably, in step S1, the rotation speed of the ball mill is 300-500 rpm, and the ball milling time is 0.5-20 h.
[0017] Preferably, in step S2, the pressing pressure is greater than 100 MPa, and the processing method includes at least one of sintering, extrusion, forging and rolling.
[0018] Preferably, in step S3, the solution temperature is 470–490°C and the solution time is 1–2 hours.
[0019] Preferably, in step S3, the temperature for artificial aging is 160–200°C, and the time is 5–12 hours.
[0020] Thirdly, the present invention provides the application of Al-Cu-Mn-C alloys with low aging heat treatment sensitivity as described in the first aspect in the aerospace field.
[0021] The beneficial effects achieved by one or more technical solutions of the present invention are as follows:
[0022] (1) Improve the heterogeneous nucleation ability of precipitates: The mechanical alloying process is used to achieve uniform dispersion of petroleum coke in Al-Cu-Mn alloy. The trace Mg element in petroleum coke atom segregates at the Al / C phase boundary, which cannot be achieved by adding C particles and Mg powder alone. This helps to increase the nucleation particles of precipitates, form ultrafine precipitates, improve material strength, and improve material plasticity.
[0023] (2) Improve the thermal stability of the precipitate phase: The Mg element in the precipitate phase of the alloy comes from petroleum coke. The precipitate phase and C particles have a strong interfacial bonding strength, which can inhibit the atomic diffusion behavior of the precipitate phase, avoid the growth behavior and agglomeration of the precipitate phase, and maintain the precipitation strengthening effect of the material. Compared with the traditional Al-Cu-Mn alloy, it has low sensitivity to aging heat treatment, friendly process control, high fault tolerance, and is suitable for industrial production.
[0024] (3) Low material and processing costs: The petroleum coke material used in this invention is a by-product of the petroleum industry. It has a large output and low cost. As an Al-Cu-Mn alloy reinforcement, it is conducive to industrial promotion and has broad application prospects.
[0025] (4) Strong technical applicability: It is compatible with other processing technologies. Attached Figure Description
[0026] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0027] Figure 1 This is a transmission electron microscope image of the precipitated phase of the T6 heat-treated Al-Cu-Mn-C alloy in Example 1 of the present invention.
[0028] Figure 2 This is a transmission electron microscope image of aluminum grains in the T6 heat-treated Al-Cu-Mn-C alloy in Example 1 of the present invention.
[0029] Figure 3 This is a scanning electron microscope image of the tensile fracture surface of the T6 heat-treated Al-Cu-Mn-C alloy in Example 1 of the present invention. Detailed Implementation
[0030] Since Watanabe proposed the concept of grain boundary engineering in 1984, grain boundary design has been extensively and deeply studied. Research has confirmed that most grain boundary phenomena are related to grain boundary diffusion and grain boundary segregation, while grain boundary structure, in turn, can influence grain boundary diffusion, segregation, and precipitation behavior. Petroleum coke, a byproduct of petrochemicals, is primarily composed of carbon (C), accounting for over 80%, and also contains trace amounts of magnesium. This helps increase the nucleation sites for precipitates, effectively improving the heterogeneous nucleation ability of 2xxx series aluminum alloys, inhibiting the growth and agglomeration of precipitates, enhancing the dispersion strengthening effect of precipitates, and thus preparing high-strength and high-toughness 2xxx series aluminum alloys.
[0031] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments and comparative examples.
[0032] Example 1
[0033] The Al-Cu-Mn matrix material used in this embodiment comprises the following components by weight percentage: Cu 3.8%, Mn 0.5%, with the balance being Al and associated elements. The Al-Cu-Mn matrix material powder is an atomized powder with an average particle size of 1 μm.
[0034] (1) Petroleum coke and Al-Cu-Mn matrix material powder were ball-milled at a mass ratio of 5:95. The ball mill rotation speed was 350 rpm and the ball milling time was 6 h to obtain Al-Cu-Mn-C alloy powder.
[0035] (2) The Al-Cu-Mn-C alloy powder was pressed at a pressure of 1300 MPa and then further extruded at a temperature of 550 °C and an extrusion ratio of 10 to obtain the extruded Al-Cu-Mn-C alloy. The yield strength, tensile strength, and elongation of the extruded Al-Cu-Mn-C alloy were 435 MPa, 564 MPa, and 11.2%, respectively.
[0036] (3) The extruded Al-Cu-Mn-C alloy was heat-treated. The heat treatment process was as follows: solution temperature 480℃, solution time 1h, water quenching after solution treatment, artificial aging at 180℃ for 10h, followed by natural cooling to obtain the T6 heat-treated Al-Cu-Mn-C alloy. The yield strength, tensile strength, and elongation of the T6 heat-treated Al-Cu-Mn-C alloy were 553MPa, 698MPa, and 10.3%, respectively.
[0037] The precipitated phases of the T6 heat-treated Al-Cu-Mn-C alloy prepared in the first embodiment were observed using transmission electron microscopy, and the results are as follows: Figure 1 As shown in the figure, the precipitated phase particles are approximately 10 nm in size and are uniformly dispersed.
[0038] The grain size of the Al-Cu-Mn-C alloy aluminum matrix in the T6 heat-treated state prepared in the first embodiment was observed using transmission electron microscopy, and the results are as follows: Figure 2 As shown in the figure, the average grain size of aluminum is 200 nm, which falls into the category of ultrafine grains.
[0039] The tensile fracture surface of the T6 heat-treated Al-Cu-Mn-C alloy prepared in the first embodiment was observed using a scanning electron microscope, and the results are as follows: Figure 3 As shown in the figure, large dimples can be observed, which is typical of ductile fracture surfaces.
[0040] Comparative Example 1
[0041] Unlike Example 1, no petroleum coke is added. The specific steps are as follows:
[0042] (1) The Al-Cu-Mn matrix material powder was ball-milled and mixed at a rotation speed of 350 rpm for 6 h to obtain ball-milled Al-Cu-Mn matrix material powder.
[0043] (2) The ball-milled Al-Cu-Mn matrix material powder was pressed at a pressure of 1300 MPa and then extruded at a temperature of 550 °C and an extrusion ratio of 10 to obtain an extruded Al-Cu-Mn alloy. The yield strength, tensile strength, and elongation of the extruded Al-Cu-Mn alloy were 365 MPa, 486 MPa, and 10.5%, respectively.
[0044] (3) The extruded Al-Cu-Mn alloy was heat-treated using the following process: solution temperature 480℃, solution time 1h, water quenching after solution treatment, artificial aging at 180℃ for 10h, followed by natural cooling to obtain the heat-treated Al-Cu-Mn alloy. The yield strength, tensile strength, and elongation of the heat-treated Al-Cu-Mn alloy were 412MPa, 568MPa, and 9.1%, respectively.
[0045] Example 2
[0046] This embodiment is basically the same as Embodiment 1, except that the artificial aging temperature is 200℃, the artificial aging time is 5h, and the material is naturally cooled after aging to obtain a heat-treated Al-Cu-Mn-C alloy with a yield strength, tensile strength and elongation of 541MPa, 684MPa and 9.6%, respectively.
[0047] Comparative Example 2
[0048] Unlike Example 2, no petroleum coke is added. The specific steps are as follows:
[0049] (1) The Al-Cu-Mn matrix material powder was ball-milled and mixed at a rotation speed of 350 rpm for 6 h to obtain ball-milled Al-Cu-Mn matrix material powder.
[0050] (2) The ball-milled Al-Cu-Mn matrix material powder was pressed at a pressure of 1300 MPa and then extruded at a temperature of 550 °C and an extrusion ratio of 10 to obtain an extruded Al-Cu-Mn alloy. The yield strength, tensile strength, and elongation of the extruded Al-Cu-Mn alloy were 365 MPa, 486 MPa, and 10.5%, respectively.
[0051] (3) The extruded Al-Cu-Mn alloy was heat-treated using the following process: solution temperature 480℃, solution time 1h, water quenching after solution treatment, artificial aging at 200℃ for 5h, followed by natural cooling to obtain the heat-treated Al-Cu-Mn alloy. The yield strength, tensile strength, and elongation of the heat-treated Al-Cu-Mn alloy were 385MPa, 523MPa, and 7.1%, respectively.
[0052] Example 3
[0053] This embodiment is basically the same as Embodiment 1, except that the artificial aging temperature is 160℃ and the artificial aging time is 12h. After aging, it is naturally cooled to obtain a heat-treated Al-Cu-Mn-C alloy with a yield strength, tensile strength and elongation of 538MPa, 679MPa and 10.3%, respectively.
[0054] Comparative Example 3
[0055] Unlike Example 3, no petroleum coke is added. The specific steps are as follows:
[0056] (1) The Al-Cu-Mn matrix material powder was ball-milled and mixed at a rotation speed of 350 rpm for 6 h to obtain ball-milled Al-Cu-Mn matrix material powder.
[0057] (2) The ball-milled Al-Cu-Mn matrix material powder was pressed at a pressure of 1300 MPa and then extruded at a temperature of 550 °C and an extrusion ratio of 10 to obtain an extruded Al-Cu-Mn alloy. The yield strength, tensile strength, and elongation of the extruded Al-Cu-Mn alloy were 365 MPa, 486 MPa, and 10.5%, respectively.
[0058] (3) The extruded Al-Cu-Mn alloy was heat-treated. The heat treatment process was as follows: solution temperature 480℃, solution time 1h, water quenching after solution treatment, artificial aging at 160℃ for 12h, followed by natural cooling to obtain the heat-treated Al-Cu-Mn alloy. The yield strength, tensile strength, and elongation of the heat-treated Al-Cu-Mn alloy were 394MPa, 537MPa, and 9.3%, respectively.
[0059] Example 4
[0060] This embodiment is basically the same as Embodiment 1, except that the Al-Cu-Mn matrix material used includes the following components by weight percentage: Cu 1%, Mn 0.5%, with the balance being Al and incidental elements. The yield strength, tensile strength, and elongation of the finally obtained heat-treated Al-Cu-Mn-C alloy are 462 MPa, 539 MPa, and 12.7%, respectively.
[0061] Example 5
[0062] This embodiment is basically the same as Embodiment 4, except that petroleum coke and Al-Cu-Mn matrix material powder are ball-milled and mixed at a mass ratio of 2:98. The yield strength, tensile strength, and elongation of the finally obtained heat-treated Al-Cu-Mn-C alloy are 426 MPa, 504 MPa, and 13.8%, respectively.
[0063] Example 6
[0064] This embodiment is basically the same as Embodiment 1, except that sintering is performed after pressing. The specific steps are as follows:
[0065] (1) Petroleum coke and Al-Cu-Mn matrix material powder were ball-milled at a mass ratio of 5:95. The ball mill rotation speed was 350 rpm and the ball milling time was 6 h to obtain Al-Cu-Mn-C alloy powder.
[0066] (2) The Al-Cu-Mn-C alloy powder was pressed at a pressure of 1300 MPa and then sintered at a temperature of 500℃ for 1 h to obtain the sintered Al-Cu-Mn-C alloy.
[0067] (3) The sintered Al-Cu-Mn-C alloy was heat-treated. The heat treatment process was as follows: solution temperature 480℃, solution time 1h, water quenching after solution treatment, artificial aging at 180℃ for 10h, followed by natural cooling to obtain the heat-treated Al-Cu-Mn-C alloy. The compressive yield strength and compressive strength of the heat-treated Al-Cu-Mn-C alloy were 457MPa and 765MPa, respectively, and it did not break at 50% compressive strain.
[0068] Example 7
[0069] This embodiment is basically the same as Example 1, except that the average particle size of the Al-Cu-Mn matrix material powder used is 200 μm. The yield strength, tensile strength, and elongation of the finally obtained heat-treated Al-Cu-Mn-C alloy are 539 MPa, 680 MPa, and 11.4%, respectively.
[0070] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A low-aging-heat-treatment-sensitive Al-Cu-Mn-C alloy, characterized in that, The composition by weight percentage is as follows: 2% to 5% petroleum coke, with the balance being Al-Cu-Mn matrix material; The Al-Cu-Mn matrix material comprises the following components by weight percentage: Cu 1.0%~3.8%, Mn 0.1%~0.5%, with the balance being Al and associated elements; The weight ratio of petroleum coke to Cu is greater than 0.8; Petroleum coke is uniformly dispersed in Al-Cu-Mn alloy, and trace amounts of Mg in petroleum coke atomically segregate at the Al / C phase boundary.
2. A method for preparing an Al-Cu-Mn-C alloy with low aging heat treatment sensitivity as described in claim 1, characterized in that, Includes the following steps: S1. Petroleum coke and Al-Cu-Mn matrix material powder are ball-milled and mixed to obtain Al-Cu-Mn-C alloy powder; S2. Press the Al-Cu-Mn-C alloy powder and process it to obtain Al-Cu-Mn-C alloy products. S3. The Al-Cu-Mn-C alloy product is solution-treated, then water-quenched, and then artificially aged. After artificial aging, it is naturally cooled to obtain the Al-Cu-Mn-C alloy with low aging heat treatment sensitivity.
3. The preparation method according to claim 2, characterized in that, The Al-Cu-Mn matrix material powder is an atomized powder with an average particle size of 1~200 μm.
4. The preparation method according to claim 2, characterized in that, In step S1, the rotation speed of the ball mill is 300~500 rpm, and the ball milling time is 0.5~20 h.
5. The preparation method according to claim 2, characterized in that, In step S2, the pressing pressure is greater than 100 MPa, and the processing method includes at least one of sintering, extrusion, forging and rolling.
6. The preparation method according to claim 2, characterized in that, In step S3, the solution temperature is 470~490 ℃ and the solution time is 1~2 h.
7. The preparation method according to claim 2, characterized in that, In step S3, the temperature for artificial aging is 160~200℃, and the time is 5~12 h.
8. The application of the low-aging heat treatment sensitive Al-Cu-Mn-C alloy as described in claim 1 in the aerospace field.
Citation Information
Patent Citations
Preparation method of nano-reinforcing metal matrix composite material with high strength and toughness
CN111500911A